2019
DOI: 10.5194/os-2019-1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of dissolved organic matter on the marine production of carbonyl sulfide (OCS) and carbon disulfide (CS<sub>2</sub>) in the Eastern Tropical South Pacific

Abstract: Oceanic emissions of the climate relevant trace gases carbonyl sulfide (OCS) and carbon disulfide (CS2) are a major source to their atmospheric budget. Their current and future emission estimates are still uncertain due to incomplete process understanding and, therefore, inexact quantification across different biogeochemical regimes. Here we present the 25 first concurrent measurements of both gases together with related fractions of the dissolved organic matter (DOM) pool, i.e. solid-phase extractable dissolv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Previous studies demonstrated large uncertainties in the global COS budget with up to fourfold on the anthropogenic source and up to 20-fold on the oceanic source. 10,[16][17][18][19]21 However, optimized values of 830±150 GgS/Yr for the oceanic source and 350±40 GgS/Yr for the industrial source, based on Monte-Carlo simulations, was suggested by Campbell et al 10 These optimized values lead to a relative contribution of 30±5% and 70±16% for the anthropogenic and oceanic sources respectively, which agrees with our independent estimate.…”
Section: Fig 4)supporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies demonstrated large uncertainties in the global COS budget with up to fourfold on the anthropogenic source and up to 20-fold on the oceanic source. 10,[16][17][18][19]21 However, optimized values of 830±150 GgS/Yr for the oceanic source and 350±40 GgS/Yr for the industrial source, based on Monte-Carlo simulations, was suggested by Campbell et al 10 These optimized values lead to a relative contribution of 30±5% and 70±16% for the anthropogenic and oceanic sources respectively, which agrees with our independent estimate.…”
Section: Fig 4)supporting
confidence: 89%
“…Recent studies suggest two approaches for the oceanic source; (1) A small oceanic source (265±210 GgS/Yr) with an additional missing source that is needed to balance the COS budget. 18,19 (2) A large oceanic source (above 800 GgS/Yr) that closes the COS budget. 9,16,17 Taking the most recent anthropogenic COS inventory of 405±180 GgS/Yr 21 together with our constraint, invokes a large oceanic source of 1200±800 GgS/Yr supporting the second approach.…”
Section: Fig 4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies estimated the direct and indirect COS marine emissions to be roughly 50%-50%, these differences may be related to natural variability. 11,18,19 Together, the direct and indirect emissions for both seas result in an isotopic value of (weighted-mean±STD) 13±2‰. Thus, we suggest this value as an initial assessment for the isotopic signal of COS emitted from seawater, under the assumption (that should be validated in further studies) of no fractionation in the oxidation processes.…”
mentioning
confidence: 75%
“…(CS 2 ) and dimethylsul de (DMS) emissions that are rapidly oxidized to COS. 9,[13][14][15] Recent studies suggested oceanic COS emissions are in the range of 200 to 4000 GgS/Yr. [16][17][18][19] The second major COS source is the anthropogenic source, which is dominated by indirect emissions derived from CS 2 oxidation -mainly from the use of CS 2 as an industrial solvent. 14,20,21 Direct emissions of COS are mainly derived from coal and fuel combustion.…”
mentioning
confidence: 99%